Konsep Matching dalam Budaya Sida Perkawinan Masyarakat Manggarai - Susana Purnamasari Baso; Maria Odriana Veronika Moi; Leopold Melkiano Triangga Dawu (Journal on Education, 2023)
This study aims to examine the applicability of the concept of matching or matching concept as well as examine the meaning of costs in the tradition of "sida perkawinan (wedding donation)" that occurs in Manggarai from an accounting perspective. Manggarai is one of the districts in East Nusa Tenggara which also has a culture of payment obligations called "sida perkawinan". This study used qualitative methods through observation and in-depth interviews with community groups in Manggarai. The results of the study show that the concept of matching or matching concepts does not apply in the culture of the “sida perkawinanan” because the meaning of cost in the “sida perkawinan” has a higher meaning, namely the value of kinship and tolerance where the elements of love, affection, caring for togetherness, solidarity, mutual assistance, and brotherhood are values ​​that are hidden behind the costs for the “sida perkawinan” and in this culture of the “sida perkawinan” Anak wina do not expect profit or benefits for the obligations that have been incurred.